HUBUNGAN KEBIJAKAN DIVIDEN DAN NILAI PERUSAHAAN PADA TAHAP MATURE DAN GROWTH - Berry, Yunike (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2016)
This paper outline and test the relationship of the dividend policy and the value of the company'smanufacturing companies listed on the Indonesia stock exchange at the mature stage and growth. Thesample use is divided into several categories. The first model predicts the whole company that pays adividend a number of 54 companies that pay dividends in the period 2010-2014, and subsequently thecompany was divided based on two-stage company growth rate that is mature and growth. This studyuse a purposive sampling method that analyzed by a panel data regression test. The results show thereis a significant positive relationship demonstrating dividend policy and corporate values that are atthe stage of mature and there is no relationship between dividend policy and the value of the companyon the growth stage of manufacturing companies in Indonesia.